2015
DOI: 10.1016/j.apsusc.2015.02.163
|View full text |Cite
|
Sign up to set email alerts
|

Understanding growth mechanisms and tribocorrosion behaviour of porous TiO2 anodic films containing calcium, phosphorous and magnesium

Abstract: The growth of the dental implant market increases the concern regarding the quality, efficiency, and lifetime of dental implants. Titanium and its alloys are dominant materials in this field thanks to their high biocompatibility and corrosion resistance, but they possess a very low wear resistance. Besides problems related to osteointegration and bacterial infections, tribocorrosion phenomena being the simultaneous action between corrosion and wear, are likely to occur during the lifetime of the implant. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 56 publications
8
73
1
9
Order By: Relevance
“…The corrosion and tribocorrosion behaviors of the anodic films synthesized in the Cβ electrolyte were undoubtedly better than for cp-Ti_Reference and PEOtreated samples in CE electrolyte. The same trend was observed by Oliveira et al [63] after tribocorrosion studies carried out in PEO-treated samples. They observed that the electrochemical behavior of all PEO-treated samples was improved as compared to cp-Ti group, from the point of view of both corrosion and tribocorrosion.…”
Section: Electrochemical Behavior and Cof Measurementssupporting
confidence: 74%
See 4 more Smart Citations
“…The corrosion and tribocorrosion behaviors of the anodic films synthesized in the Cβ electrolyte were undoubtedly better than for cp-Ti_Reference and PEOtreated samples in CE electrolyte. The same trend was observed by Oliveira et al [63] after tribocorrosion studies carried out in PEO-treated samples. They observed that the electrochemical behavior of all PEO-treated samples was improved as compared to cp-Ti group, from the point of view of both corrosion and tribocorrosion.…”
Section: Electrochemical Behavior and Cof Measurementssupporting
confidence: 74%
“…x behavior was also reported by Oliveira et al [63]. All PEOtreated samples in CE electrolyte displayed lower OCP values and so, higher corrosion tendency, when compared to samples treated in the Cβ electrolyte.…”
Section: Electrochemical Behavior and Cof Measurementssupporting
confidence: 66%
See 3 more Smart Citations